Die Keimzelle transformative Praxen einer anderen Stadtgesellschaft. Theoretische und künstlerische Zugänge - Haarmann, Anke 1968-; Lemke, Harald 1965- (Urban Studies, 2021)
Gardening together, becoming subsistent, shaping the city, living art and at the same time reflecting on the utopian sense or nonsense of this activity that was the motto of the neighbourhood garden "Keimzelle" (engl. nucleus) (2011-2019) in Hamburg. In this context, the contributors to the volume provide a strong theoretical basis as well as an artistically vivid examination of the transformative potential of DIY urban spaces. Accompanied by a skilled discourse community, the artistic approach makes a multidimensional penetration of transformative practice tangible. And in the interaction of critical scholarship and political initiative, the possibilities of alternative urban development become clear